A global classification and characterization of earthquake clusters. Issue 1 (8th August 2016) - Zaliapin, Ilya; Ben-Zion, Yehuda
Abstract: We document space-dependent clustering properties of earthquakes with m ≥ 4 in the 1975–2015 worldwide seismic catalogue of the Northern California Earthquake Data Center. Earthquake clusters are identified using a nearest-neighbour distance in time–space–magnitude domain. Multiple cluster characteristics are compared with the heat flow level and type of deformation defined by parameters of the strain rate tensor. The analysis suggests that the dominant type of seismicity clusters in a region depends strongly on the heat flow, while the deformation style and intensity play a secondary role. The results show that there are two dominant types of global clustering: burst-like clusters that represent brittle fracture in relatively cold lithosphere (e.g. shallow events in subduction zones) and swarm-like clusters that represent brittle–ductile deformation in relatively hot lithosphere (e.g. mid-oceanic ridges). The global results are consistent with theoretical expectations and previous analyses of earthquake clustering in southern California based on higher quality catalogues. The observed region-specific deviations from average universal description of seismicity provide important constraints on the physics governing earthquakes and can be used to improve local seismic hazard assessments.